1971
DOI: 10.1364/ao.10.002162
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Speed Photography of Picosecond Light Pulses and Echoes

Abstract: Three new results have been obtained with a recently developed camera of 10-psec framing time: (1) The effect of the finite speed of light in photographing relativistic objects is experimentally demonstrated, by photographing a dumbbell-like entity formed by two packets of light. In contrast to material objects, which, theory predicts, should appear rotated, the light dumbbell appears sheared. (2) Photographs of the mode-locked Nd: glass laser radiation show numerous subsidiary pulses accompanying the main ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(46 citation statements)
references
References 28 publications
0
45
0
1
Order By: Relevance
“…3 A variety of methods have been developed to extract the ballistic light from the background of scattered light. Among these are spatial f iltering techniques 5 and incoherent 6,7 and coherent 8,9 methods that take advantage of the temporal stretching of a short pulse of light in a scattering medium.…”
mentioning
confidence: 99%
“…3 A variety of methods have been developed to extract the ballistic light from the background of scattered light. Among these are spatial f iltering techniques 5 and incoherent 6,7 and coherent 8,9 methods that take advantage of the temporal stretching of a short pulse of light in a scattering medium.…”
mentioning
confidence: 99%
“…These pioneering studies demonstrated an ultrafast optical shutter using the laser induced Kerr effect which could "photograph light in fl ight". Figure 1.3 shows a schematic of Duguay's ultrahigh speed Kerr shutter photographing an ultrashort light pulse propagating though a scattering solution of diluted milk [ 9 ]. The Kerr shutter operates by using an intense laser pulse to induce birefringence (the Kerr effect) in an optical medium placed between two crossed polarizers.…”
Section: Photographing Light In Flightmentioning
confidence: 99%
“…If the induced birefringence is electronically mediated, it has an extremely rapid response time and the Kerr shutter can achieve picosecond or femtosecond time resolution. Optical scattering limits the ability to image biological tissues, and Duguay proposed that an ultrahigh speed shutter could remove the unwanted scattered light and detect light echoes from inside tissue [ 9 ]. Ultrahigh speed optical shutters might be used to "see through" tissues and therefore to non-invasively image internal pathology.…”
Section: Photographing Light In Flightmentioning
confidence: 99%
“…Another important application of a light gate is ballistic imaging through a highly scattering medium, such as milky water-alcohol mixture [8]. The high speed light gate was implemented using nonlinear optical Kerr effect with a CS 2 cell, thus the opening shutter time of the light gate is about the same as the laser pulse width (~10ps as reported in [8]).…”
Section: Introductionmentioning
confidence: 99%